An economic evaluation of alternative test-intervention strategies to prevent fetal growth restriction in singleton pregnancies. (16th November 2010) - Morris, RK; Malin, GL; Tsourapas, A; Roberts, TE; Khan, KS
Abstract : Aim: To investigate the potential cost-effectiveness of alternative 'test and treat' strategies in the prevention of fetal growth restriction compared to a strategy of no screening in the UK. Methods: Economic evaluation using a decision tree model based on data from systematic reviews in a population of all pregnant women with subgroup analysis based on population risk. Setting of clinics, General Practices, Health Centres or any setting delivering antenatal care to pregnant women. The main outcome measure was cost-effectiveness based on an outcome of fetal growth restriction avoided. Results: 105 studies were reviewed on the accuracy of six different tests; Cochrane reviews were used for effectiveness data of possible 42 interventions. Cost data were based on secondary evidence, supplemented with primary data from local sources. Testing prior to intervention was not shown to be the most cost-effective strategy in the analyses for all pregnant women and low risk women. Antiplatelet therapy, without prior testing, was highlighted as potentially cost-effective in preventing fetal growth restriction in these populations. In high risk women, testing with serum human chorionic gonadotrophin followed by antiplatelet therapy in those that test positive was a potentially cost-effective strategy. Interpretation: An effective, affordable and safe intervention applied to all mothers without prior testing is likely to be the most cost-effective strategy in the prevention of fetal growth restriction. The results reported in this paper are important for prioritising future research, worldwide.